Is the third sputum smear really necessary for the Diagnosis of Pulmonary Tuberculosis? - ATIQA AMBREEN AAMIR RAHIM ZAIB UN NIS, ABDUR RAHMAN (Journal of Fatima Jinnah Medical University, 2018)
Objective: The purpose of this study was to assess the value of examining multiple sputum specimens in maximizing the sensitivity of detection of Mycobacterium tuberculosis, Place and duration of study: From Jan 2009- Dec 2009. Subjects and Methods: Three sputum smear microscopy of patients suspected of tuberculosis was performed under DOTS at Gulab Devi Hospital, Lahore from Jan 2009- Dec 2009. Results: 5711 persons were sputum smear positive for AFB in the time period analyzed. 84.5% persons (4823 of 5711) had 1st specimen positive for AFB, 9.7%, (557 of 5711) had second specimen positive and the third specimen was positive for only 5.7% (331 of 5711). Conclusions: This study indicates that the first and the second specimen enable M. tuberculosis detection from a majority of patients (94.3%), while the third or a subsequent specimen collected is of little diagnostic relevance (5.7%). These findings substantially agree with the recent WHO recommendation that the number of specimens to be examined for screening of TB cases can be reduced from three to two.